Trends and Findings in Trajectory Studies: a Methodological Approach to Classify Labor Development - Mariela Sonia Jiménez Vásquez (Universidad Autónoma de Baja California, 2009)
Trajectory studies are a methodological option that helps to completely analyze labor paths forged by individuals in the labor market. However, when initiating a research in this topic there are several different scopes, discipline approaches, objects and purposes of research, which hinder its comprehension. This article presents the main trends established to guide this type of research and some of the theoretical and methodological elements found in its structure.